Analysis of Domestic Content Standards for 5G BTS Infrastructure in Indonesia Using RIA Method - Sekar Wangi, Insani; Setyo Arifin, Ajib (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to analyze and develop the standards for the Domestic Content Level (DCL) specifically for 5G Base Transceiver Station (BTS) infrastructure in Indonesia using the Regulatory Impact Analysis (RIA) method. The Regulatory Impact Analysis (RIA) method is employed as the primary approach in this research to evaluate various policy options and potential DCL standards for implementation. This approach allows for understanding the policy implications on various stakeholders, including regulators, vendors, and operators. A cost-benefit analysis assessment was conducted using in-depth interview methods, and the results indicate that the status quo alternative, which is 40% DCL standards for goods and services components, remains relevant for implementation in Indonesia. On the other hand, regulators are evaluating and reviewing this regulation with the aim of increasing the DCL value and fostering BTS industry in Indonesia. The challenges currently faced by local producers also require stronger government supervision and support for future technological self-sufficiency in Indonesia.